Graphene-Based Nanomaterials for Photothermal Therapy in Cancer Treatment - Daniela F. Báez (MDPI AG, 2023)
Graphene-based nanomaterials (GBNMs), specifically graphene oxide (GO) and reduced graphene oxide (rGO), have shown great potential in cancer therapy owing to their physicochemical properties. As GO and rGO strongly absorb light in the near-infrared (NIR) region, they are useful in photothermal therapy (PTT) for cancer treatment. However, despite the structural similarities of GO and rGO, they exhibit different influences on anticancer treatment due to their different photothermal capacities. In this review, various characterization techniques used to compare the structural features of GO and rGO are first outlined. Then, a comprehensive summary and discussion of the applicability of GBNMs in the context of PTT for diverse cancer types are presented. This discussion includes the integration of PTT with secondary therapeutic strategies, with a particular focus on the photothermal capacity achieved through near-infrared irradiation parameters and the modifications implemented. Furthermore, a dedicated section is devoted to studies on hybrid magnetic-GBNMs. Finally, the challenges and prospects associated with the utilization of GBNM in PTT, with a primary emphasis on the potential for clinical translation, are addressed.